The Virtual Museum and Female Joy in Argentina: An Exploration of the Revolt - Losiggio, Daniela; Taccetta, Natalia (Intermédialités / Intermediality, 2021)
In reviewing the theory of the museum, art historian Griselda Pollock proposes a “virtual feminist museum,” a gallery that does not exist but proves formidable indeed. According to Pollock, the institutions where art circulates are governed by patriarchal logics of exhibition and conservation. This article considers the potential contents of a virtual Latin American feminist museum. The widespread Argentinian feminist movement #NiUnaMenos (2015) and the National Campaign for the Right to Safe, Free, and Legal Abortion (since 2005) yielded a vast corpus of images. In an unprecedented way in Argentina, these images extended traditional public spaces (parks, streets, and assembly) by incorporating digital media (especially social networks). In a circular fashion, the images themselves—especially photos—demonstrated enormous power to call on people to rise up and take to the streets. The hypothesis we present here is that the power belonging to these images is associated with a new pathos of female enjoyment (glitter and makeup, nudity and joy) that constitutes a virtual Latin American feminist museum.